Effect of 12 months of testosterone replacement therapy on metabolic syndrome components in hypogonadal men: data from the Testim Registry in the US (TRiUS) - Bhattacharya, Rajib K.; Khera, Mohit; Blick, Gary; Kushner, Harvey; Nguyen, Dat; Miner, Martin M. (BMC Endocrine Disorders, 2011)
Recent evidence suggests that there may be a bidirectional, physiological link between hypogonadism and metabolic syndrome (MetS), and testosterone replacement therapy (TRT) has been shown to improve some symptoms of MetS in small patient populations. We examined the effect of 12 months of TRT on MetS components in a large cohort of hypogonadal men.